Central arterial stiffness and diastolic function are associated with insulin resistance and abdominal obesity in young women but polycystic ovary syndrome does not confer additional risk - Emma Rees (Human Reproduction, 2014)
Some studies have found that young women with polycystic ovary syndrome (PCOS) have increased measures of cardiovascular (CV) risk. However, PCOS is associated with insulin resistance (IR) and obesity which are themselves associated with increased risk of CV disease. Therefore in this population it is difficult to establish how much of the risk is due to IR and obesity rather than PCOS per se and this may have implications for management of the syndrome. We conducted a cross-sectional study to determine whether subclinical CV dysfunction in young women with PCOS is independent of the effects of obesity. 84 women with PCOS (Rotterdam criteria) and 95 healthy volunteers (16-45 years) were enrolled in the study and underwent detailed assessment of body composition, endocrinology status, arterial and cardiac function. Methods included computed tomography assessment of visceral fat, arterial tonometry measures of stiffness, carotid ultrasound measures of intima-media thickness and echocardiographic measures of diastolic function. After adjustment for age and body mass index, PCOS subjects had greater insulin response following glucose challenge and higher testosterone levels but similar measures of arterial stiffness, carotid intima-media thickness and diastolic function. PCOS subjects had unexpectedy higher levels of high-molecular weight adiponectin (thought to be cardio-protective) but there was no significant relationship between adiponectin and arterial stiffness or diastolic function. Central arterial stiffness and diastolic dysfunction are associated with both IR and obesity in young women but PCOS does not appear to confer additional risk. Therefore obesity represents the greatest modifiable risk factor for CV disease in young women with PCOS and lifestyle measures which target weight reduction are critical in the management of the syndrome.